Anna-szignumok Tolsztoj és Kosztolányi prózájában: Adalékok az Anna Karenina és az Édes Anna koreferenciális vizsgálatához - Kovács, Árpád (Studia Litteraria, 2018)
The study approaches the interpretation of the two novels with the tools of prose poetics. It unfolds the manifestations of the isomorphy of the name and the text at the level of narration, metaphorical meaning and semantic innovations. It explores the coreferential operation that can be perceived between the text interior and the texts, and also the source texts of these entities in the subject of judgment and mercy. From a generic perspective, the interference of the epic novel, the thesis novel, and the sacral discourse gains more attention, along with their polemic character as opposed to the norms of political utterance. With regards to the symbolic systems of both novels, the study thoroughly examines the central role of the interrelations of love, corporeality and spirituality, and also their coreferential connections to the poetics of Charis and Charisma. The poetic relevancies of the two writers’ statements are also explored, so that the fundamentals of their unique literary anthropology can be enlightened.